1997
DOI: 10.2307/30141246
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Policies at Children's Hospitals regarding Immunity of Healthcare Workers: Are Physicians Protected?

Abstract: Children's hospitals vary widely in their policies regarding healthcare-worker immunity, and, in many cases, physicians may not be protected from nosocomial transmission of community infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Although our institution's lack of inclusion of physicians in an employee-health program may not represent the norm, many other children's hospitals also fail to include physicians, as evidenced by our previous publication. 8 These findings identify a need to intensify employee-health measures to comply with national recommendations. Healthcare facilities are not mandated by national recommendations, Centers for Disease Control and Prevention guidelines, or OSHA regulations to include hospital-based non-employee physicians in employeehealth programs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although our institution's lack of inclusion of physicians in an employee-health program may not represent the norm, many other children's hospitals also fail to include physicians, as evidenced by our previous publication. 8 These findings identify a need to intensify employee-health measures to comply with national recommendations. Healthcare facilities are not mandated by national recommendations, Centers for Disease Control and Prevention guidelines, or OSHA regulations to include hospital-based non-employee physicians in employeehealth programs.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, only 58% of children's hospitals required evidence of annual TB screening among physicians. 8 In another survey, 28% of pediatric emergency medicine physicians reported that they had not received a TB skin test within 1 year of the survey. 4 In our hospital, annual TB screening of employees is mandatory; however, at the time of this survey, it was not required of physicians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In a survey of infection control professionals from pediatric hospitals, 90% reported HCP exposures to pertussis over a 5-year period; at 11% of the reporting institutions, a physician contracted the disease. 8 Multiple outbreaks of pertussis have been reported in healthcare facilities. 5 For example, a community outbreak in Rochester, Minnesota, led to an outbreak at the Mayo Clinic in which 64 HCP developed pertussis.…”
Section: Discussionmentioning
confidence: 99%
“…11 ' 12 In a 1994 survey of ICPs from 62 children's hospitals, 90% reported having had at least 1 case of pertussis at their hospital during the past 5 years, and 11% reported that physicians acquired pertussis because of exposure to a patient with the disease. 23 Most outbreaks were the result of a failure to recognize and isolate infected patients or a failure to rapidly diagnose and treat pertussis in HCWs and implement control measures. 24 Failure to suspect the diagnosis is especially relevant in pediatric settings, owing to the fact that pertussis in infants may not be suspected at the first medical encounter because early symptoms (ie, gagging, gasping, cyanosis, bradycardia, and apnea) may precede or overshadow cough.…”
Section: Discussionmentioning
confidence: 99%